2017
DOI: 10.1007/s10544-017-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell-laden microgel prepared using a biocompatible aqueous two-phase strategy

Abstract: Microfluidic methods are frequently used to produce cell-laden microgels for various biomedical purposes. Such microfluidic methods generally employ oil-water systems. The poor distribution of crosslinking reagents in the oil phase limits the available gelation strategies. Extracting the microgel from the oil-phase also reduces its production efficiency. In this study, an aqueous two-phase system (ATPS) involving dextran (DEX) and polyethylene glycol (PEG) was used to prepare cell-laden microgel. This avoided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Depending on variables such as the relative position of microchannels, the rate of injection, number of liquids used, and their viscosity, different kinds of shapes can be achieved. In addition, encapsulation of cells can be achieved by incorporating them in the desired precursor solution (usually the one that will adopt a microstructure) prior to their injection into the microfluidic channel [117,118]. More complicated microfluidic devices can be used to obtain structures such as core-shell spheres, hollow tubes, osteon-like microfibers (Fig.…”
Section: Microfluidicsmentioning
confidence: 99%
“…Depending on variables such as the relative position of microchannels, the rate of injection, number of liquids used, and their viscosity, different kinds of shapes can be achieved. In addition, encapsulation of cells can be achieved by incorporating them in the desired precursor solution (usually the one that will adopt a microstructure) prior to their injection into the microfluidic channel [117,118]. More complicated microfluidic devices can be used to obtain structures such as core-shell spheres, hollow tubes, osteon-like microfibers (Fig.…”
Section: Microfluidicsmentioning
confidence: 99%
“…The production of sphere-shaped cellulose-based microparticles can be performed by emulsification processes [ 93 , 112 , 113 , 114 , 115 ], and microfluidics technology [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ], as well as other less common techniques, namely spray-assisted techniques [ 126 , 127 , 128 , 129 , 130 ], and the LbL assembly [ 131 , 132 ]. Concerning the cellulosic substrate, the majority of the studies reported the utilization of cellulose derivatives, such as CMC [ 120 , 131 ], CA [ 114 , 119 ] and EC [ 123 , 124 , 133 , 134 ], but also pristine vegetable cellulose [ 112 , 135 , 136 , 137 ], bacterial nanocellulose [ 116 , 117 , 118 ] and microcrystalline cellulose (MCC) [ 93 , 115 , 138 , 139 ]. The preference for cellulose derivatives to generate microparticles was anticipated given their solubility in water or in most common organic solvents, which translates into simpler processability.…”
Section: Production Of Spherical Cellulose-based Microparticlesmentioning
confidence: 99%
“…48,49 Based on this control, several microfluidic devices have been optimized to use aqueous two-phase systems to generate spheroids. [50][51][52][53] This approach is based on the use of a polymeric ATPS (DEX/PEG) to confine the cells within a nanolitre-volume aqueous drop immersed within a second, immersion aqueous phase in close proximity, and cells aggregate to spontaneously form a spheroid. The commonly used bioavailable ATPS is polyethene (PE) and dextran (DEX) due to the strong partition of cells to dextran in this system.…”
Section: Aqueous Two-phase System (Atps)mentioning
confidence: 99%
“…An ATPS consisting of DEX and PEG was reported for the preparation of a cell-laden microgel using microfluidic devices, which involved a periodically changing injection force. 50,52 The microfluidic devices will overcome the issue of low interfacial tension between the two phases. The microfluidic device chamber can pump out fluids with different injection conditions, which can control the size of droplets.…”
Section: Aqueous Two-phase System (Atps)mentioning
confidence: 99%